2023
DOI: 10.29333/ejmste/13140
|View full text |Cite
|
Sign up to set email alerts
|

The effect of computer simulations on students’ conceptual and procedural understanding of Newton’s second law of motion

Abstract: This study aims to assess the impact of computer simulations (CSs) within an inquiry-based learning (IBL) environment on grade 11 students’ performance in Newton’s second law of motion (NSLOM). The study sample consisted of 90 male and female students selected from a population of two public schools in Al Ain city in United Arab Emirates (UAE). The study employed a pre- and post-test quasi-experimental design involving four equally distributed grade 11 physics classes: two as experimental groups (EGs) (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Learning simulations demonstrate superior cost-efficiency compared to offline simulations and traditional training methods. The findings of this study are consistent with the conclusions drawn from previous research conducted by various scholars [36][37][38][39][40]. The studies' findings revealed that students showed a significant interest in and openness to using simulation programs in the context of online education at tertiary institutions.…”
Section: Discussionsupporting
confidence: 91%
“…Learning simulations demonstrate superior cost-efficiency compared to offline simulations and traditional training methods. The findings of this study are consistent with the conclusions drawn from previous research conducted by various scholars [36][37][38][39][40]. The studies' findings revealed that students showed a significant interest in and openness to using simulation programs in the context of online education at tertiary institutions.…”
Section: Discussionsupporting
confidence: 91%